Integration of Scientific and Social Literacy through the Project to Strengthen Pancasila Student Profiles in Elementary Schools - Ustazah Mutiara As'Zaroh; Ratnasari Diah Utami (Jurnal Ilmiah Sekolah Dasar, 2023)
The Ministry of Education and Culture has made many independent curriculum modifications that impact teaching methodology. One is in the context of science and social studies, which are combined into one unified whole. Therefore, teachers must implement learning innovations that combine social and scientific literacy as one of the basic activities for students to become more familiar with integrating science and social before science content. This research examines integrating scientific literacy and social literacy competencies through a project program to strengthen the profile of Pancasila students in elementary schools. With a combination of field and literature studies, this research uses a qualitative methodology. With the subject of research, teachers, students, and principals. How to collect data through observation, documentation, and interviews. By using several sources, multiple method triangulation, and data analysis at the stages of data reduction, data presentation, and conclusion, the accuracy of the data was tested. The study results show that integrating scientific literacy and social literacy through project activities to increase students' Pancasila profiles can run well. In addition, integrating scientific literacy and social literacy can achieve the goal of project implementation, which is a form of adaptation activity for students before entering science and social studies content in an independent curriculum.